UNLOCKING POTENTIAL: GEOGRAPHICAL BRANDING AS A POSSIBLE FACTOR OF REVITALIZATION OF SERBIAN VILLAGES – A CASE STUDY OF THE VISOK MICROREGION - Radivojević, Aleksandar; Marković, Rastko; Marković, Ksenija; Langović, Ana; Marjanović, Miloš; Stojilković, Filip; Filipović, Ivan; Lukić, Tin (Economics of Agriculture, 2024)
The objective of this paper is to emphasize, branding as one of the possible ways to take concrete steps towards reaffirming the local values and traditional knowledge of rural populations in Serbia. Based on information gathered in the field, as well as from existing literature sources, the main goal of this study is to promote products from the Visok microregion. Due to very alarming demographic data, this may be the last chance for revitalizing this region. In this study, we highlighted the following products: Pirot kilim (Pirot rug), Pirot/Stara Planina lamb, Pirot Kachkaval cheese, Stara Planina honey, and Stara Planina potato. Besides agriculture, micr oregion Visok also has exceptional tourist potential. The conclusion of this paper emphasizes that the only viable path to revitalization is through planned investment. Such investment would facilitate the development of local infrastructure and help restore the population, thus enabling the creation of sustainable development.